Rules, Discretion, and Central Bank Independence: The German Experience 1880 - 1989 - Bernard Eschweiler; Michael D. Bordo (Rutgers University, Department of Economics, 1993)
Theories of rules and discretion have become a corner stone in the formulation of macroeconomic policy. They suggest that monetary policy rules are first best in terms of social welfare. However, if commitment is not feasible, delegating monetary policy to an independent and conservative central bank can be second best. Monetary policy in Germany during the past one hundred years provides an excellent case to assess the empirical evidence on the use of rules and central bank independence in monetary policy making. Since the creation of a central monetary authority in 1876, Germany has participated in four monetary regimes: the pre-war gold standard, the inter-war gold standard, the Bretton Woods system, and the floating exchange rate regime. With the exception of the two world war periods German monetary policy was geared primarily towards maintaining price stability and characterized by a high degree of formal and practical central bank independence
Keywords: E5; 330; central bank independence; discretion; Germany; rules